Redescription of Anaschisma (Temnospondyli: Metoposauridae) from the Late Triassic of Wyoming and the phylogeny of the Metoposauridae. (1st February 2020) - Gee, Bryan M.; Parker, William G.; Marsh, Adam D.
Abstract : Metoposaurids are non-marine temnospondyls that are among the most common constituents of Late Triassic deposits, but despite their abundance, the evolutionary relationships of the group are poorly resolved and have not been fully addressed with modern phylogenetic methods. The genus Anaschisma is one of a number of poorly resolved metoposaurid taxa and was erected to describe two species from the Popo Agie Formation (Carnian) in Wyoming: Anaschisma browni and Anaschisma brachygnatha . Since being named, the genus has been repeatedly synonymized and separated with other taxa in the context of broader revisions of the Metoposauridae. At present, Anaschisma is considered to be an indeterminate metoposaurid. Extensive descriptive work of metoposaurids since the erection of Anaschisma in 1905 and the last taxonomic review of the clade in 1993, including the naming of several new taxa and the reappraisal of several others, has generated a sufficiently detailed database through which to re-evaluate the taxonomy of the Metoposauridae as part of the analysis of phylogenetic relationships of Anaschisma . Here we reappraise and redescribe the holotypes of A. browni and A. brachygnatha to determine their taxonomic status and relationships in the context of an updated and revised metoposaurid phylogenetic framework. Anaschisma browni and Anaschisma brachygnatha are synonymized under the former species, as all previously listed diagnostic differences are compatible with intraspecific variation. Additionally, the well-known Koskinonodon perfectus is found to be a junior synonym of Anaschisma browni, which takes taxonomic precedence given its earlier description. Poor phylogenetic resolution of the Metoposauridae is likely the product of marked morphological conservatism within the clade and limited character sampling, although some patterns of regional clustering are apparent from the analysis.